Associations in Conflict - Casas, Sandra I.; Perez-Schofield, J. Baltasar García; Marcos, Claudia A. (INFOCOMP Journal of Computer Science, 2007)
Aspect-Oriented Programming (AOP) is an emergent technology for the modularization of crosscutting concern. The most used approach to support the AOP paradigm is based on the aspect notion, as the basic unit that contains the crosscutting concern logic and a method that relates it to the functional components (pointcuts, advices, join-points). This mechanism, popularized by tools like AspectJ, restricts and limits the handling of conflicts among aspects. In this work a flexible, wider and powerful approach is presented. This strategy is based on two main mechanisms: definition of associations and explicit rules. The approach presented is implemented in a prototype denominated MEDIATOR.